Identitas nasional: Krisis identitas nasional generasi z dalam kehidupan sosial kontemporer - windiyanti, arin kamal (Maliki Interdisciplinary Journal, 2026)
The advancement of the digital era and the accelerating tide of globalization have posed serious challenges to the formation of national identity, particularly among Generation Z. This study aims to analyze the national identity crisis experienced by Generation Z in contemporary social life, examine the contributing factors, and formulate adaptive strategies for strengthening national identity in accordance with the characteristics of the digital native generation. The method employed is a systematic literature review drawing on various relevant scientific sources. The findings reveal that social media plays an ambivalent role with respect to national identity: on one hand, it has the potential to reinforce national awareness; on the other, it risks shifting the cultural orientation of young people toward globalism. The values of Pancasila as the foundation of national identity face serious challenges due to the weakening of their internalization among the younger generation. Strengthening national identity requires a comprehensive approach encompassing adaptive civic education, critical digital literacy, the strategic use of technology, and synergy among the government, educators, and society at large.